O ENCONTRO NO ATO DE COMERMOS JUNTOS: uma análise do anúncio publicitário #eattogether - Cunha, Raquel Cantarelli Vieira da (2021)
When we feed off of Anthropology to improve a research on Communication, we face different perspectives about the act of eating. The present article is the result of a few reflections proposed in the Anthropology of Eating, which focused on the research about the meeting that is promoted by the act of having a meal together. We believe that we have been negligent about meals. Not in the aspect of what is eaten, but on how we behave in such an everyday act. This perception reinforces our hypothesis that there are many aspects involved in the ritual of eating a meal together that deserve our attention, since many things happen when people eat together. Therefore, the interaction promoted by the environment created around the act of eating was problematized in a time structure, under a perspective of table rituals. Consequently, an analysis was made of the video #eattogether, which inaugurates the day of eating together. It was noticed that a meal eaten together can create a form of resistance to the mediated communication. Moreover, the meeting promoted by the act of eating together configures a space to rescue interpersonal communication, to reflect on the symbolic value of being with the other and it strengthens social ties.